Asymmetrical roles and conflicting expectations in institutional talk: an analysis of verbal autopsy - Doroja-Cadiente, Glenda; Gustilo, Leah (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study addresses the research gap in doctor-death informant interactions within verbal autopsy (VA) contexts, examining these interactions as unequal encounters through institutional interaction research. The study aims to analyse the content, structure, and function of question-and-answer exchanges in VA interviews, explore conflicting frames, and identify opposing discursive strategies. It connects microanalysis to the broader sociocultural context, viewing VA as a regulatory practice reflecting local health unit procedures. Data were collected from 64 death informants and two rural municipal health physicians in Northern Leyte, Philippines. Interviews were conducted using WHO's Standardised Verbal Autopsy guide, and the interactions were transcribed and analysed for topic, question type, question-answer sequence, and alignment with institutional roles. The study reveals that doctors, as institutional authorities, control the interaction, with informants recognising this asymmetry through honorifics and apologies. Conflicting frames of expectations between doctors' objective questioning and informants' subjective responses lead to interactional struggles. These struggles are exacerbated by the informants' emotional instability, potentially compromising the reliability of death reports. The overwhelming VA process challenges doctors' decision-making capabilities, leading to the imposition of institutional authority. The study highlights the need for VA training that considers the psycho-socio-cultural contexts of informants to improve the quality of health information systems. Understanding interactional barriers and implementing research-based communication strategies can enhance doctor-informant relationships and institutional protocols. Policymakers might better address the need for context-sensitive VA training. Future research could explore variations in death reporting across different regions and the psychological experiences of doctors and informants.